The effect of pitch size manipulation during small sided-games performed by different age category football players: a pilot study - Espada, Mário C.; Gamonales, José M.; Verardi, Carlos E. L. [UNESP]; Filho, Dalton M. Pessôa [UNESP]; Ferreira, Cátia C.; Robalo, Ricardo A. M.; Dias, Amândio A. P.; Hernández-Beltrán, Víctor; Santos, Fernando J. (MRE Press, 2023)
This research aimed to analyse the pitch size manipulation effect on internal and external load and to study the age effect on the studied variables in different small-sided games (SSGs) formats. Male U-12 (n = 8), U-15 (n = 8) youth football players, and U-23 (n = 8) professional cohorts participated in the study. Two SSGs formats were analyzed, goalkeeper (GK) + 4 vs. 4 + GK, 3 minutes play in 20 × 30 m and 24 × 36 m, with 3 minutes rest between bouts. The variance analysis Anova two-way was used to analyse two independent factors, pitch size, and age group. The playing area manipulation had an effect under the following variables: distance (p < 0.001), speed 0–6 km/h (p < 0.001), speed 12–18 km/h (p < 0.001), speed 18–21 km/h (p < 0.001), accelerations (Ac.) 1–2 m/s2 (p < 0.001), decelerations (Dc.) 2–3 m/s2 (p < 0.001), metabolic power (Pmet) (p < 0.001) and high metabolic load distance (HMLD) (p < 0.001). The age group influenced the distance covered (p < 0.001), speed 0–6 km/h (p < 0.001), speed 6–12 km/h (p < 0.001), speed 12–18 km/h (p < 0.001), speed 21–24 km/h (p = 0.030), Ac. 1–2 m/s2 (p < 0.001), Ac. 1–2 m/s2 (p < 0.001Pmet (p < 0.001), HMLD (p < 0.001) and training impulse (TRIMP) (p < 0.001). Playing area manipulation in football SSGs promotes an increase in external load intensity, namely, larger areas are suitable for larger effects at high speeds (>21 km/h) and TRIMP. A careful and detailed evaluation of training tasks, considering the different age category football players, is important to optimize the planning in football, aiming at improving players’ condition and performance and avoiding health problems and injuries.
Keywords: External load; Global positioning system; Internal load; Reduced games; Training